Determinants of Organic Tea Cultivation and Selection of Efficient Marketing Channels by the Orthodox Tea Growers in Nepal - Simkhada, S.; Kattel, R. R.; Dhakal, S. C.; Koirala, A. (Journal of the Institute of Agriculture and Animal Science, 2020)
The trend of organic agriculture in developing countries has increased due to increasing health consciousness of consumers and high demand for organic products in developed countries. However, the rate of conversion to organic production is much slower than in other countries and the tea farmers who work hard all-around a year have not got proper market share due to several reasons. The study was conducted in Suryodaya municipality, Sakejung, Jasbire, Maipokhari, and Sandakpur area of the Ilam district by purposively and randomly selecting 160 tea farmers for questionnaire survey to determine the socio-economic and institutional factors that play a significant role in organic cultivation practice and selection of effective marketing channels. The data were collected from the interview with farmers, direct observation, focus group discussions and key informant interviews using pre-tested semi-structured questionnaires. The average gross margin per kilogram green leaf was NRs. 17.16 for organic and NRs. 13.15 for conventionally produced ones. The decision of farmers to practice organic orthodox tea production and selection of efficient marketing channel in the study areas was estimated through the Logit model. The involvement of farmers in cooperative and marketing channels followed for the marketing of green leaves and farming years significantly affected the organic cultivation of orthodox tea. The study revealed that the marketing channel; producers–cooperatives–processors–retailers– consumers was found to be the most efficient. The ethnicity, farming experience, and organic production of tea significantly affected the selection of an efficient marketing channel by orthodox tea farmers.